Schistophleps kendricki sp. nov. (Lepidoptera: Erebidae: Arctiinae) from Bangladesh with an overview of the genus - Rayhan, Md Jahir; Bucsek, Karol; Jahan, Sayema (Zootaxa, 2024)
Schistophleps Hampson, 1891 is one of the most frequently occurring genera of tiger moths, widely distributed in the Oriental and Australian regions. However, a lion’s share of the species belonging to this genus are poorly known except the original descriptions. In this article, we provide a brief overview of all known species currently assigning to this genus. We divide the species into albida, bicolora, bipuncta, flavia, fulvia, hyalina, and subtilis species groups on the basis of wing pattern elements along with geographic distributions, and four highly obscure species are discussed as a miscellaneous group. Among the species, Schistophleps bipuncta Hampson, 1891 is the most frequently occurring taxon having a distribution stretching all over the South East Asia. However, the variable wing maculations and other features, reflected through the observations on various citizen science platforms from different regions of the Indian subcontinent indicate to a sibling species yet to discover. Herein, we describe the species as Schistophleps kendricki Rayhan, Bucsek, & Jahan sp. nov., from Chittagong, Bangladesh that is similar to the Schistophleps bipuncta species group in wing maculation, but markedly differs from all of its closely allied congeners in the genitalia configurations in having characteristic modification of uncus. Besides, a comparison of observations on different citizen science platforms from the Indian subcontinent is provided that suggests the possible distribution of this new species throughout the Bengal including West Bengal, India and Bangladesh.